Value chain analysis of medicinal plants in Geoparks: Livelihoods of ethnic minorities based on non-timber forest products (NTFPs) in Vietnam. - An Thinh Nguyen; Kien Huy Ngo; Nam Xuan Ngo; Ngoc Anh Le; Ngoc Trinh Phuong; Do Thi Thao; Huyen Trang Le; Chi Linh Vu; Thi Toan Luu; Van Quy Khuc; Hao Thi Nguyen; Duc Bao Nguyen (PLoS ONE, 2025)
Non-timber forest products (NTFPs) support the livelihoods and economic activities of households and communities in both rural and urban areas worldwide. This study applies the value chain analysis (VCA) approach to Jiaogulan (Gynostemma pentaphyllum), a local NTFP in the Cao Bang Geopark, Vietnam. A semi-structured questionnaire was used to survey 106 stakeholders involved in different stages of the Jiaogulan value chain, including agricultural experts (extension officers and farmer association representatives), harvesters, traders, primary processors, secondary processors, distributors, and consumers. The findings present a comprehensive mapping of the Jiaogulan value chain, illustrating the flow of the product from harvest to end consumer and quantifying the added value at each stage of the process. The study highlights the value captured by households involved in the primary market channels and assesses how this added value contributes to household income levels. The distribution of economic benefits across different actors within the value chain is also examined, identifying potential inefficiencies and disparities that need to be addressed to improve equity and economic outcomes for marginalized groups. Recommendations are made to strengthen production and cooperation among Jiaogulan value chain actors through technical training, infrastructure investment, e-commerce development, and policy support for international standards and medicinal value chains to enhance product quality, market access, and sustainable development in Cao Bang Geopark.